2009
DOI: 10.1152/japplphysiol.91262.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise intensity and volume on persistence of insulin sensitivity during training cessation

Abstract: The purpose of this study was to determine whether exercise prescriptions differing in volume or intensity also differ in their ability to retain insulin sensitivity during an ensuing period of training cessation. Sedentary, overweight/obese subjects were assigned to one of three 8-mo exercise programs: 1) low volume/moderate intensity [equivalent of approximately 12 miles/wk, 1,200 kcal/wk at 40-55% peak O(2) consumption (Vo(2peak)), 200 min exercise/wk], 2) low volume/vigorous intensity ( approximately 12 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
90
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 30 publications
6
90
1
4
Order By: Relevance
“…Previous studies in humans and rodents have reported increased insulin sensitivity after either higher-intensity or longer-duration acute exercise protocols than used in the present study (3,8,15,19,23,34,43,44,54). The exercise intensity achieved in the present study by sheep in the intensive exercise test (30 min, 8% slope, 4 -4.4 km/h) is probably ϳ50 -60% of V O 2max , based on studies in pregnant sheep (26).…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies in humans and rodents have reported increased insulin sensitivity after either higher-intensity or longer-duration acute exercise protocols than used in the present study (3,8,15,19,23,34,43,44,54). The exercise intensity achieved in the present study by sheep in the intensive exercise test (30 min, 8% slope, 4 -4.4 km/h) is probably ϳ50 -60% of V O 2max , based on studies in pregnant sheep (26).…”
Section: Discussionsupporting
confidence: 47%
“…However, evidence is accumulating that differences exist in the individual response to exercise training. On average, approximately 15-20% of people failed to improve their glucose tolerance and insulin sensitivity after exercise training interventions (7); this nonresponse is not restricted to a specific type of exercise (endurance or resistance training or combinations), although differences are reported (8)(9)(10)(11).…”
Section: Tgf-b Contributes To Impaired Exercise Response By Suppressimentioning
confidence: 99%
“…Several studies have indicated that training-related improvements in insulin action are retained after 10 days without physical activity in master athletes (Rogers et al 1990), and after 15 days of inactivity in overweight/obese subjects (Bajpeyi et al 2009). However, to our knowledge, there is no other information concerning the retention characteristics of insulin action after various exercise prescriptions in T2DM.…”
mentioning
confidence: 99%
“…Higher volumes of exercise (i.e., more weekly sessions) may induce more changes in the skeletal muscle mitochondrial content compared with lower-volume exercise regimens of the same intensity (65-85% V 4 O 2peak ) 15 days after training cessation (Bajpeyi et al 2009). However, there is a debate about the magnitude of exerciseinduced changes in skeletal muscle mitochondrial content as a function of exercise intensity (40-55% vs. 65-85% O 2peak ) so this deduction should be treated with caution (Bajpeyi et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation